The Influence of Wedding Events and MICE Activities on Food and Beverage Revenue at Samudra Indah Resort & SPA Hotel - UTAMA, I Wayan Nanda Asa; TUWI, I Wayan; MARENI, Ni Ketut (PT Keberlanjutan Strategis Indonesia, 2026)
Hotels are service-oriented businesses; therefore, they are expected to meet all guest needs, including food and beverage services. One of the efforts to increase revenue in this sector is by optimizing the organization of wedding events and MICE activities. The problem addressed in this study is whether the organization of wedding events and MICE activities significantly influences food and beverage revenue at Samudra Indah Resort & Spa Hotel (name changed). The purpose of this study is to examine the influence of wedding events and MICE activities on food and beverage revenue. This research uses a quantitative approach with multiple linear regression analysis. Data were collected through documentation studies and processed using SPSS software. The results of the study show that, based on the multiple linear regression calculation, the equation obtained is Y = 2.617 + 0.580X1 + 0.415X2. Wedding events and MICE activities partially influence food and beverage revenue, as indicated by the t-value > t-table. Simultaneously, both variables have a positive and significant effect, as shown by the F-value > F-table. The coefficient of determination shows that wedding events and MICE activities influence food and beverage revenue by 44.5%, while the remaining 55.5% is affected by other factors not examined in this study.